Nano-Chitosan and Aschorbic Acid Synergistically Combat Resistant Staph in Atopic Dermatitis: Nano-Kitosan dan Aschorbic Acid Secara Sinergis Memerangi Staph Resisten pada Dermatitis Atopik - Jaafar Ali Muhammad; Assoc.Prof. Dr. Adawia Fadhil Abbas Alzubaidi; Khaled Al-Hussein Muhammad Idris; Mutaman A. A. Kehail (Academia Open, 2024)
Chitosan, derived from natural sources like fish scales and fungal cell walls, forms nanoparticles (NPs) with notable antimicrobial properties. This study examines the antibacterial effects of ascorbic acid combined with nano-chitosan on Staphylococcus aureus isolates from 100 atopic dermatitis (AD) patients. Using the Vitek 2 Compact device for bacterial identification and antibiotic sensitivity testing, we found that nano-chitosan/ascorbic acid composites significantly inhibited the growth of multidrug-resistant S. aureus. The antimicrobial activity increased with higher concentrations, highlighting the potential of this natural polymer blend as an effective treatment for AD-related bacterial infections. Highlights: Effective Inhibition: Nano-chitosan/ascorbic acid inhibits multidrug-resistant Staphylococcus aureus. AD Focus: Targets S. aureus in atopic dermatitis patients. Green Alternative: Uses natural, non-toxic antibacterial agents. Keywords: Chitosan nanoparticles, Ascorbic acid, Staphylococcus aureus, Atopic dermatitis, Antibacterial treatment